Torsional capacity of reinforced concrete U-shaped walls. (June 2021) - Hoult, Ryan
Abstract: Reinforced concrete U-shaped walls are embedded within buildings internationally and can provide the primary lateral resistance to buildings in the events of high winds or earthquakes. In such events, these types of walls are not only expected to deform laterally but have the potential to twist. There is a limited amount of research that has focused on the torsional performance of reinforced concrete walls. Furthermore, the current methods for the design of torsion in modern building codes cannot be applied directly to open sections governed by warping torsion. This research investigates the torque capacity of reinforced concrete U-shaped walls. A parametric study is undertaken to find the torque capacity of U-shaped core walls with a large range of typical design parameters. Using the results from the parametric study, a nonlinear regression analysis is used to formulate a simple expression to determine an approximation of the torsional strength capacity of RC U-shaped walls.